PENDAMPINGAN IDENTIFIKASI POTENSI EKONOMI MELALUI PENDEKATAN MARKET SYSTEM DEVELOPMENT DI KECAMATAN JABUNG, KABUPATEN MALANG - Athoillah, Moh.; Pimada, Laila Masruro; Yuana, Pusvita; Paksi, Girindra Mega (Jurnal Abdi Insani, 2024)
The development of a village in Indonesia is currently often neglected by the local government so that development is focused on urban areas. Therefore, it is necessary to map the economic potential of a village in order to become a reference for the government in providing appropriate policies. One of the sub-districts in Malang Regency that has a variety of potential villages, namely Kecamatan Jabung. Jabung sub-district has an area of approximately 135.89 km2. Jabung sub-district consists of 15 villages, each of which has problems in efforts to improve welfare, especially in Jabung Village and Kemiri Village. Kemiri Village has a main commodity, robusta coffee, with production reaching more than 700 tons. In addition, most of the people in Jabung Village work as dairy farmers. In addressing the existing problems and potential, the author conducted a mapping of the economic potential in Jabung and Kemiri Villages. This research uses descriptive research based on market system development framework that provides a description and explanation of the mapping of economic potential in Jabung Village and Kemiri Village, Malang Regency. This article has implications in the mapping of economic potential in Jabung Village and Kemiri Village, Malang Regency, East Java, namely the results of coffee in Kemiri Village and cow's milk in Jabung Village which can be a recommendation for local government policy or other areas that have the same potential, this can have an impact on the optimization of the potential of Jabung Village and Kemiri Village, also increase the economy in Jabung Village.